Responsible entrepreneurship: outlining the contingencies. Issue 3 (18th April 2019) - Vallaster, Christine; Kraus, Sascha; Kailer, Norbert; Baldwin, Brooke
Abstract : Purpose: The purpose of this paper is to give an up-to-date assessment of key topics and methods discussed in the current literature on responsible entrepreneurship. In the past years, sustainable development itself has become a more popular and important topic in the academic literature and hence the field of sustainable entrepreneurship has become a greater topic of interest and opportunity for solution. Therefore, a systematic literature review is conducted to assess new contributions to the field and its potential for the future of sustainable development, with a focus on responsible innovation. Design/methodology/approach: Systematic, evidence-informed literature review following Tranfield et al. (2003). Findings: Based on a conceptual literature review, five streams of research that responsible entrepreneurs distinguish from purely for-profit entrepreneurs are identified and discussed: walking the line between profit creation and value creation for society; business models of responsible entrepreneurs; their role in transforming society; getting ready to innovate responsibly; and the role of market incentives to foster sustainable business practices. Originality/value: The structured literature review allows to identify future research paths. In detail, ideas as regards the management of upcoming tensions when trying to combine profit creation and value creation for society, and finally, the way innovation processes need to be rethought when innovating responsibly are discussed and outlined.